Kampanye Jakarta Bersih untuk Meningkatkan Kesadaran Masyarakat agar Tidak Membuang Sampah Sembarangan pada saat CFD di Bundaran HI - Anita Fitri Wahyudi; Dinah Ainiyyah; Kirana Safira; Safira Aprilia; Dini Safitri (Jurnal Pengabdian Pada Masyarakat, 2020)
THE JAKARTA BERSIH CAMPAIGN TO RAISE PUBLIC AWARENESS SO AS NOT TO DISPOSE OF LITTER DURING CFD AT THE HI ROUNDABOUT. Car Free Day is an activity held every Sunday. It was held on May 23, 2002. Currently it continues for 5 hours starting from 06.00 - 11.00 WIB. Car Free Day aims to socialize to the public to reduce private vehicles so that people are interested in using public transportation. The implementation is along the road in the Central Jakarta area, precisely around Senayan - Monas. People who take part in this activity usually spend time exercising, selling, or running their community activities. The various activities carried out on the car free day cause a lot of waste. Not all visitors of the car free day are aware of the importance of keeping the environment clean. On May 5, 2019 we held a campaign called "Jakarta Bersih" by inviting visitors of car free day to dispose of garbage in its place. We toured the roundabout area of ​​HI by carrying trash bags, posters and stickers for the campaign. Some visitors approached us to dispose of their trash. Visitors who have supported the campaign were given stickers. Then we interviewed a number of visitors to find out their opinions about the garbage scattered in the CFD area and how the solution was.